(untitled) (Revista Educação, Artes e Inclusão, 2022)
This article aimed to understand which are and how they are articulate the teaching knowledge of the musical-pedagogical practice of the licensed teacher in Music, of the curricular component Art, of the final years of Elementary Education, in schools of the Mossoró (RN) state education system. For this study, we chose to adopt the qualitative approach, appropriating the case study. The data were constructed through semi-structured interviews, documentary research and observations. The theoretical framework of the research is based on studies on teaching knowledge by Tardif (2014), on some studies in the area of ​​education, such as Freire (1996) and Pimenta (1996), and music education, such as Beineke (2000) and Beaumont (2003). The results demonstrate that the knowledge present in the pedagogical-musical practice of the final years of Elementary Education is diverse. Such knowledge is acquired through pre-professional training, which includes the knowledge of family experience; school life and musical trajectory; professional training for teaching, including initial and continuing training courses; they come from textbooks, as well as produced and validated by the teaching practice itself. It was noticed that knowledge is integrated into teaching practice in different ways and is mobilized according to the situations of the teaching profession.